Microalgae toxins in food products and impact on human health: a review - Withana, W. A. T. N.; Gunarathna, D. M. D. I.; Dissanayake, D. M. G. I.; Rathnayake, A. I.; de Zoysa, H. K. S.; Waisundara, Viduranga Y. (Frontiers in Nutrition, 2025)
Microalgal toxins are secondary metabolites synthesized by cyanobacteria, dinoflagellates, and diatoms in response to environmental stress. Humans and animals can be exposed to these toxic compounds through food, water, and aerosolized toxins and these toxic compounds are capable of causing acute and chronic health issues like paralysis, liver damage, cancer, and even death by employing several molecular mechanisms such as sodium channel blocking, protein phosphatase inhibition, cellular membrane disruption etc. Microalgal toxin poisoning through food products is a major concern as microalgae are largely consumed as dietary supplements. These toxins can easily bioaccumulate and be biomagnified via food chains. Hence, proper screening and quality control measures for these microalgal toxins should be implemented. Cytotoxins, dermatoxins, neurotoxins, hepatotoxins, and endotoxins are the main toxins produced by the microalgae. Microalgae are effectively incorporated into the food industry in a diverse range. Toxic contaminants from the microalgae are a silent threat to food security and human health. There are some regulatory models when consuming microalgae-related food products and water due to their toxic effects. Detecting the toxins in the initial stage, studying the impact of toxin production due to environmental factors, and developing effective mitigation strategies to ensure food safety, is a future needs in this field.